Optimizing uni-compartmental knee arthroplasty: the impact of preoperative planning and arithmetic hip-knee-ankle angle - Changquan Liu; Cheng Huang; Xin Suyalatu; Qidong Zhang; Yiling Zhang; Wei Sun; Wanshou Guo; Weiguo Wang (BMC Musculoskeletal Disorders)
Abstract Purpose The purpose of this study was to evaluate whether the combination of preoperative planning software combined with arithmetic hip-knee-ankle angle (aHKA) can help patients who underwent uni-compartmental knee arthroplasty (UKA) recover the constitutional alignment of the lower limb, obtain a better prosthetic position, and achieve better early patient-reported outcome measurements (PROMs). Methods A total of 150 patients who underwent UKA (planning group: 50 patients using the preoperative planning software; conventional group: 100 patients using the conventional method) were included in the study. The aHKA was defined as 180° + mechanical medial proximal tibial angle (MPTA) - mechanical distal lateral femoral angle (LDFA). All patients in the planning group underwent UKA according to the planning software with the planned lower limb alignment of aHKA. All patients were divided into three groups: constitutional alignment group (postoperative HKA (post-HKA): aHKA ± 2.0°); overcorrection group (post-HKA > aHKA + 2.0°); under-correction group (post-HKA < aHKA − 2.0°). Comparisons between the planning and conventional groups were conducted: (1) the proportion of post-HKA restored to constitutional alignment group; (2) the postoperative prosthesis position parameter based on the guideline of the Oxford group; (3) the American Knee Society scores (KSS) at six months after surgery. Results The proportion of the constitutional alignment group in the planning group was higher than that in the conventional group (86% vs. 66%) (p = 0.033). There was no significant difference in postoperative prosthesis position parameters between the two groups. No significant difference was found between the KSS clinical score (91.02 ± 4.20 vs. 90.61 ± 4.24) and KSS functional score (86.10 ± 7.23 vs. 84.30 ± 6.82) in six months after surgery between the planning and conventional groups. Conclusion Patients who underwent UKA using preoperative planning software in combination with aHKA were able to recover a higher proportion of the constitutional alignment than those with the conventional method. In addition, the planning group could achieve similar postoperative prosthesis position and short-term PROMs compared to the conventional group. Clinical trial number Not applicable.